2020
DOI: 10.1182/bloodadvances.2020002049
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic proapoptotic effect of PARP-1 and HDAC inhibition in cutaneous T-cell lymphoma is mediated via Blimp-1

Abstract: The therapy of advanced mycosis fungoides (MF) presents a therapeutic challenge, and the search for new therapeutic targets is ongoing. Poly(ADP-ribose) polymerase 1 was shown to be upregulated in patients with advanced MF and could be druggable by a new class of chemotherapeutic agents, PARP-1 inhibitors, which are already in clinical trials for other malignancies; however, the role of PARP-1 inhibitors in MF has never been established. We examined the efficacy of talazoparib in the murine model of cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…HDACi therapy has already been shown to have positive effects on aggressive CTCL types. HDACis in combination with other therapy, such as chemotherapeutic drugs, immunomodulatory drugs, monoclonal antibody, may provide a novel treatment option that can improve clinical outcomes in patients with CTCL ( 34 , 35 , 57 , 70 , 131 133 ) ( Table 2 ). Currently, more and more HDACI combination therapy regimens are undergoing clinical trials, indicating the important role of HDACi drug in the treatment of CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…HDACi therapy has already been shown to have positive effects on aggressive CTCL types. HDACis in combination with other therapy, such as chemotherapeutic drugs, immunomodulatory drugs, monoclonal antibody, may provide a novel treatment option that can improve clinical outcomes in patients with CTCL ( 34 , 35 , 57 , 70 , 131 133 ) ( Table 2 ). Currently, more and more HDACI combination therapy regimens are undergoing clinical trials, indicating the important role of HDACi drug in the treatment of CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Kruglov et al. reported that Parp1 inhibition increased the expression of Irf8 and Bcl6 , leading to upregulation of Blimp1 and Bax and subsequently restraining DNA repair in cutaneous T cell lymphoma ( Kruglov et al., 2020 ). Another study reported that Bcl6 directly regulates Bach2 expression and Ung expression ( Alinikula et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The model is largely inflammation dependent, and resolution of inflammation leads to the resolution of lymphoma. While BALB/c mice do not support implantation of MBL2 tumors, B6.SJL mice can be easily inoculated with MBL2 without underlying inflammatory microenvironment (Table 2) [74,[81][82][83]. Mishra et al, (2016) evaluated the role of an inflammatory cytokine IL-15 in CTCL using IL-15 transgenic (Tg) mice that developed skin inflammation with some features reminiscent of human MF.…”
Section: Gemm and Other Important Ctcl Mouse Modelsmentioning
confidence: 99%